Environmental Diseases in the Context of Climate Change: A Systematic Review - Borges Ximenes, Eliseba; Barreto Guterres, Celsea Suave; Maia Macedo, Maria Estela; Ximenes de Deus, Calistro; Faria Marçal, Suzi Bernardina; Guterres Magno, Nuno Pedro (Rifa'Institute, 2026)
Introduction: Climate change exerts a significant impact on human life and health globally. As a preeminent global health issue of the 21st century, climate change alters ecosystems, environmental conditions, and disease transmission patterns. These impacts represent a profound challenge to global public health infrastructure. Objective: This study aims to systematically review the relationship between climate change and environmentally mediated diseases. Method: This research employs the Systematic Literature Review (SLR) approach, adhering to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Data were retrieved from six scientific databases: Google Scholar, PubMed, ScienceDirect, Scopus, Semantic Scholar. Results and Discussion: The findings indicate that climate variability including extreme temperatures, high humidity, flooding, drought, and air pollution plays a pivotal role in elevating the risk of various environmentally mediated diseases. The most frequently reported conditions include diarrhea, dengue fever, respiratory tract infections, scabies, cholera, and leptospirosis. Conclusion: Integrated climate change mitigation and adaptation strategies are essential. These must be coupled with the strengthening of public health systems, improved sanitation, and the development of community-based disaster preparedness to protect high-risk groups from the health-related consequences of climate change.